Optical genome mapping identifies a germline retrotransposon insertion in SMARCB1 in two siblings with atypical teratoid rhabdoid tumors. Issue 2 (29th July 2021) - Sabatella, Mariangela; Mantere, Tuomo; Waanders, Esmé; Neveling, Kornelia; Mensenkamp, Arjen R; van Dijk, Freerk; Hehir‐Kwa, Jayne Y; Derks, Ronnie; Kwint, Michael; O'Gorman, Luke; Tropa Martins, Madalena; Gidding, Corrie EM; et al.
Abstract: In a subset of pediatric cancers, a germline cancer predisposition is highly suspected based on clinical and pathological findings, but genetic evidence is lacking, which hampers genetic counseling and predictive testing in the families involved. We describe a family with two siblings born from healthy parents who were both neonatally diagnosed with atypical teratoid rhabdoid tumor (ATRT). This rare and aggressive pediatric tumor is associated with biallelic inactivation of SMARCB1, and in 30% of the cases, a predisposing germline mutation is involved. Whereas the tumors of both siblings showed loss of expression of SMARCB1 and acquired homozygosity of the locus, whole exome and whole genome sequencing failed to identify germline or somatic SMARCB1 pathogenic mutations. We therefore hypothesized that the insertion of a pathogenic repeat‐rich structure might hamper its detection, and we performed optical genome mapping (OGM) as an alternative strategy to identify structural variation in this locus. Using this approach, an insertion of ~2.8 kb within intron 2 of SMARCB1 was detected. Long‐range PCR covering this region remained unsuccessful, but PacBio HiFi genome sequencing identified this insertion to be a SINE‐VNTR‐Alu, subfamily E (SVA‐E) retrotransposon element, which was present in a mosaic state in the mother. This SVA‐E insertion disrupts correct splicing of the gene, resulting in loss of a functional allele. This case demonstrates the power of OGM and long‐read sequencing to identify genomic variations in high‐risk cancer‐predisposing genes that are refractory to detection with standard techniques, thereby completing the clinical and molecular diagnosis of such complex cases and greatly improving counseling and surveillance of the families involved. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.